Deadbeat predictive power control for Vienna rectifier under unbalanced power grid condition. (November 2021) - Lu, Yiyan; Liu, Zhao; Meng, Shuai; Ji, Jiawei; Lyu, Jianguo
Abstract: Due to the low output distortion and switch voltage stress, Vienna rectifiers have been widely utilized in high-power applications such as communication power supplies, wind power systems and electric vehicle charging piles. However, Vienna rectifiers still have to face tough challenges under unbalanced grid considering the inherit operating range limitation caused by its structure. Consequently, a deadbeat predictive power control (DBP-PC) for the Vienna rectifier under unbalanced grid is proposed. Using the positive and negative sequence double dq decoupling current control strategy, the operating range of the Vienna rectifier under unbalanced grid is analyzed. Furthermore, an improved DBP-PC for Vienna rectifiers under unbalanced grid is proposed. By the improved DBP-PC, the stable operating range can be effectively extended. Finally, the corresponding simulations and experiments are executed to demonstrate the performance of the proposed control strategy.